FUNCTIONAL TRANSFORMATION OF WEST MORAVA VALLEY DISTRICT SETTLEMENTS - Penjisević, Ivana; Dragojlović, Jovan (Bulletin of Natural Sciences Research, 2020)
The existing territorial layout and the current demographic situation in the settlements of West Morava Valley District during the late 20th century and at the beginning of the 21st century are the result of the synchronized action of the process of industrialization, deagrarization and urbanization. They conditioned the selective transformation of urban and rural space, which led to the concentration of the population in urban and suburban settlements and the depopulation of the rural part of the West Morava Valley District. Within the studied region, the hierarchy of municipal centers, subcenters and communities of settlements was observed. Based on important theoretical and methodological assumptions and indicators, the paper analyzes the functional transformation of the settlements of West Morava Valley in the period between 1971- 2011. It was determined by certain quantitative methods that the changes went in the direction of reducing the share of purely agrarian settlements and increasing the share of industrial and service settlements.
Keywords: West Morava Valley District; Settlements Network; Business structures; Functional transformation of settlement